Surgical treatment of obstipation due to metabolic bone disease in a Savannah Monitor - Ts. Chaprazov (Bulgarian Journal of Veterinary Medicine)
Metabolic bone disease (MBD) syndrome is a common finding in reptiles kept in terrariums. This clinical case describes the diagnosis, surgical treatment and antibacterial therapy of obstipation result-ing from MBD syndrome in a Savannah monitor (Varanus exanthematicus), referred to the Small Animal Clinic of the University Veterinary Hospital, Stara Zagora, Bulgaria. The monitor was pre-sented with a history of ataxia, anorexia and lack of defecation from several months. MBD syndrome and a colon obstructed with faecoliths were confirmed clinically, by radiology and computed tomography. The surgical treatment comprised celiotomy, followed by colon enterotomy to remove the faecal masses and closure of the body wall. The post-operative period and the recovery of the patient were without complications.